Incorporating the joint toxicity of co‐applied pesticides into the ecological risk assessment process. (28th July 2017) - Belden, Jason B; Brain, Richard A
ABSTRACT: Pesticides are frequently formulated as mixtures of active ingredients. Although traditionally ecological risk assessments (ERAs) have focused on individual active ingredients, there is an ongoing effort in many jurisdictions to more formally include assessment of mixtures. The overall goal of this project was to describe an approach for conducting ERA of jointly applied pesticides. We suggest that standard testing of formulation mixtures is not warranted due to the low probability of synergy occurring at a high‐enough magnitude to be measurable above experimental variability. Thus, empirical testing should focus on formulations for which there is a greater likelihood of synergy due to known toxicological interactions of the pesticide class or a priori knowledge of synergy, such as intellectual property claims. Additionally, empirical testing should focus on species that are above levels of concern and limit testing on species for which it is unlikely that synergy would significantly change the outcome of the ERA. If empirical testing is warranted, we suggest that results be compared to the concentration addition model (CA). If the empirical data deviates from the model by a factor of greater than 5, then synergy is considered likely and the ERA is based on the empirical data. Otherwise, the ERA may use CA to calculate risk quotients or be based on the most toxic active ingredient. To evaluate the approach, we reviewed formulation mixtures for which data were available. Only 3 of 24 mixture studies were found to deviate from CA by more than 5. The majority of the studies had a single component that dominated toxicity, suggesting that the ERA for these formulations will not be meaningfully different if based on the most toxic active ingredient. Overall, this approach balances risk assessment conservatism and reduces testing that would likely not result in improvement of the ERA. Integr Environ Assess Manag 2018;14:79–91. © 2017 SETAC Key Points: Expanded standard testing of formulation mixtures is not warranted due to the low probability of synergy occurring at a high‐enough magnitude to be measurable above experimental variability. Empirical testing should focus on formulations for which there is a greater likelihood of synergy due to known toxicological interactions of the pesticide class or a priori knowledge of synergy, such as from intellectual property claims. If empirical testing is warranted, we suggest that results be compared to the concentration addition model (CA). Only 3 of 24 case studies deviated from the CA model by more than 5×, and the majority had a single component that dominated toxicity, suggesting the ERA for 21 of 24 studies would not greatly change if it is based on the most toxic component.